2022
DOI: 10.3390/photonics10010003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Large-Area Diffractive Lens Using Multiple Sub-Aperture Diffractive Lenses and Computational Reconstruction

Abstract: Direct imaging systems that create an image of an object directly on the sensor in a single step are prone to many constraints, as a perfect image is required to be recorded within this step. In designing high resolution direct imaging systems with a diffractive lens, the outermost zone width either reaches the lithography limit or the diffraction limit itself, imposing challenges in fabrication. However, if the imaging mode is switched to an indirect one consisting of multiple steps to complete imaging, then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…An optical experiment was carried out with a laboratory model of telescope. 28 A spatially incoherent light source (Thorlabs, 170 mW, λ = 650 nm and Δλ = 20 nm) was used for illumination of objects. A 10 μm pinhole was used for recording the PSF and an USAF object (Group -5, Element 1) number 5 and gratings with a line width of 15.63 μm was used as the test object.…”
Section: Methodsmentioning
confidence: 99%
“…An optical experiment was carried out with a laboratory model of telescope. 28 A spatially incoherent light source (Thorlabs, 170 mW, λ = 650 nm and Δλ = 20 nm) was used for illumination of objects. A 10 μm pinhole was used for recording the PSF and an USAF object (Group -5, Element 1) number 5 and gratings with a line width of 15.63 μm was used as the test object.…”
Section: Methodsmentioning
confidence: 99%
“…A positive photoresist (AR-P 3510T, Allresist) was spin coated on the substrate at 4000 rpm for 60 s, followed by a soft bake on a hot plate at 100 o C for 60 s. A Maskless Aligner (Heidelberg Instruments µMLA) with precise dose control of the light source λ = 390 nm was used for photoresist exposure. After exposure to UV light, the mask was developed in AR 300-44 (Allresist) and rinsed in ultrapure water [38]. The duration of exposure for a single mask is ~1 hr.…”
Section: Preliminary Experiments With Diffractive Optical Elements Fa...mentioning
confidence: 99%
“…26 The performance of LRRA was found to be better than NLR and LRA when implementing deterministic optical fields. 27,28,29 Recently, several methods were reported to tune AR independent of LR using Bessel, Airy and self-rotating beams. 30,31,32 In this study, we proposed and demonstrated two hybridization methods HM-1 and HM-2 for engineering AR independent of LR both in real time and post recording.…”
Section: Introductionmentioning
confidence: 99%